Language development and social emotions in children with speech delay: case study of 9 year olds in elementary school - Fitriyani Fitriyani; Mohamad Syarif Sumantri; Asep Supena (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
This research was conducted to describe language development and social-emotional behavior that affect children with speech delays, ranging from early detection of language and speech problems, intervention programs, academic development in schools and social-emotional development and accompanying factors. children with late talk. This study is based on observations of a 9-year-old child, conducted from September 2018 to January 2019, with several data acquisitions since 2012 when early detection of language disorders and speech. It conducted the study using a qualitative approach with a case study method. Collecting data through observation, interviews and document studies. This study describes develop children with problems with speech and language delay (speech delay), seen from the cognitive, affective and psychomotor aspects and the influence of their social-emotional behavior. The findings in this study are social-emotional behaviors that have a major influence on develop children with language delay disorders, which require intervention programs suitable with the support of the family and the surrounding environment.